Dynamic changes in the sperm quality of Mytilus galloprovincialis under continuous thermal stress. Issue 2 (29th December 2015) - Boni, Raffaele; Gallo, Alessandra; Montanino, Melania; Macina, Alberto; Tosti, Elisabetta
SUMMARY: Global warming is an increasingly serious problem underlying ecological change in marine flora and fauna. Mytilus galloprovincialis is an intertidal species that colonizes coasts in moderate and warm climates, and can thus withstand extreme climatic conditions; however, it successfully reproduces only within a certain temperature range. The effects of prolonged exposure to 28°C, a temperature unsuitable for breeding activity, on sperm quality were evaluated in this study. Such heat stress induced the following: a significant reduction in concentration; a biphasic pattern of motility and mitochondrial membrane potential that first increased, and then collapsed; a decrease in the intracellular calcium concentration; a rapid increase in lipid peroxidation that was normalized after the third week of heat stress; an increase in DNA fragmentation after the third week of heat stress; and atypical morphology (i.e., sperm with a globular head, asymmetrical tail, and acrosome loss). Currently, these elevated‐temperature conditions are achieved along the Mediterranean coast during the late summer, when the reproductive activity of M. galloprovincialis is suspended after massive spawning in the spring. The increasing global temperature, however, may shift their breeding season, thus significantly impacting marine ecosystems and mussel production. Mol. Reprod. Dev. 83: 162–173, 2016. © 2015 Wiley Periodicals, Inc .